Pax and the politics of peace : Republic to Principate - Cornwell, Hannah (Oxford classical monographs, 2017)
The concept of Roman peace (pax) did not just denote the absence of war but formed part of a much greater discourse on how Rome conceptualized herself. This volume explores its changing meaning from Republic to Principate, arguing that it is fundamental to understanding the shifting balance of power and the creation of the Roman Empire